Association between NLRP3 Inflammasome and Tumor-Node-Metastasis Staging in Prostate Cancer: Immunohistochemical Studies of Prostate Needle Biopsy and Radical Prostatectomy Specimens - Miyauchi, Toshiya; Narita, Shintaro; Saiki, Yuriko; Kudo-Asabe, Yukitsugu; Horii, Akira; Fukushige, Shinichi; Habuchi, Tomonori; Nanjo, Hiroshi; Goto, Akiteru (The Tohoku Journal of Experimental Medicine, 2024)
The pathological role of NLRP3 inflammasome in prostate cancer (PCa) remains unclear. This study aimed to elucidate the expression of its major components in PCa by immunohistochemistry and its clinicopathological significance. An immunohistochemical analysis of 184 prostate needle biopsy and 38 radical prostatectomy specimens from PCa revealed the expression status of NLRP3, PYCARD, and caspase-1, which form NLRP3 inflammasome. Furthermore, the association between the expression of these 3 proteins and the clinical parameters at diagnosis and operation was analyzed. In biopsy specimens, the Cochran-Armitage test demonstrated that the proportion of the high expression of NLRP3 (P < 0.001) and PYCARD (P < 0.001) in cancerous tissue tended to increase as the value of the Gleason Grade Group increased, and immunohistochemistry of NLRP3 and PYCARD helped to distinguish cancerous tissue from adjacent noncancerous tissue in some cases. Furthermore, a univariable logistic regression analysis revealed the high expression of NLRP3 to be associated with clinical T3–4 (P = 0.0056) and distant metastasis at diagnosis (P = 0.011), while the high expression of PYCARD was associated with clinical T3–4 (P < 0.001), regional lymph node metastasis (P < 0.001), and distant metastasis at diagnosis (P < 0.001). However, a multivariable logistic regression analysis showed no significant association. In prostatectomy specimens, no significant association existed between the expression of NLRP3 inflammasome and the clinical parameters at operation, partly due to the influence of neoadjuvant chemohormonal or hormone therapy. In conclusion, these results suggest that NLRP3 inflammasome may promote disease progression and metastasis in PCa, therefore immunohistochemistry of NLRP3 and PYCARD could be useful for diagnosing PCa accurately.